International Human Resource Strategy and Its Determinants: The Case of Subsidiaries in Taiwan - Hannon, John M.; Huang, Ing-chung; Jaw, Bih-Shiaw (Journal of International Business Studies, 1995)
This paper explores how the tension between global integration and local responsiveness affects the dimensions and determinants of international human resource (IHR) strategy. To accomplish this, Jarillo and Martinez's [1990] business strategy framework for parents and their subsidiaries was recast in an IHR strategy setting. Then, the relationships between the two dimensions of IHR strategy that emerged, global integration and local responsiveness, and a set of interorganizational interdependency variables were explored. Several new and informative associations between the interorganizational interdependency variables (subsidiaries' dependence on parent's resources, local resources, and hot institutions) and IHR strategy were observed in a sample of one hundred subsidiaries of Japanese, U.S. and European MNCs operating in Taiwan.